Immune Checkpoint Inhibition in Marjolin Ulcer: A Case Series. Issue 6 (July 2021) - Shalhout, Sophia Z.; Kaufman, Howard L.; Sullivan, Ryan J.; Lawrence, Donald; Miller, David M.
Abstract : Immunotherapy has revolutionized the treatment of advanced cutaneous squamous cell carcinoma. However, the role of immune checkpoint inhibitors for the treatment of Marjolin ulcer (MU), a rare cutaneous malignancy that arises from previously traumatized and chronically inflamed skin, is not well defined. Thus, efficacy and clinical response to immunotherapy in patients with MU requires further investigation. MU with squamous cell carcinoma, the most commonly associated malignancy, is highly aggressive with a greater risk for lymph node and distant metastasis compared with non-MU cutaneous squamous cell carcinoma. Often associated with nonhealing chronic wounds from burn scars, injuries, venous stasis ulcers, osteomyelitis, and radiotherapy, MU carries a poor prognosis. We conducted a retrospective study and describe a single institution experience of patients with MU treated with anti–programmed cell death protein 1 (PD-1) therapy at Massachusetts General Hospital between 2016 and 2020. Five subjects with this rare presentation met inclusion criteria and were treated with pembrolizumab (N=2) or cemiplimab (N=3). Four subjects received immunotherapy in the first-line setting. Notably, 1 patient had durable disease control for 1 year while on immunotherapy, with continued disease control after the cessation of anti-PD-1 therapy. Of the 4 patients that progressed on anti-PD-1 therapy, disease control at 5 months was achieved in 2 patients. Furthermore, 60% overall survival (3 patients) was observed in this limited cohort at 12 months after initiating anti-PD-1 therapy for MU. We describe the clinicopathologic features and clinical outcomes of our MU-SCC cohort.